Effect of dryer & drying methods and production time on the quality and safety of dried yoghurt during storage - Khadir Abdelhakam, Khadir Ebrahim; Alhad Alhady, Altayeb Tagaldein Ahmed; Osman, Fatin Hassan; Ibrahim, Ibrahim Aldaw` (Proceeding ICMA-SURE; Vol 1 No 1 (2021): Proceeding ICMA-SUREDO - 10.20884/2.procicma.2021.1.1.4424, 2021)
The main objective of this research is to study the effect of drying, drying methods and production time on the quality & safety of dried yoghurt and effect of storage on it.   4 kg of natural yoghurt freshly produced during the first day of shelf life, and 4 kg after expiration date (day 11), the samples were dried using two method, spray drying process and the traditional method, dried yoghurt samples were stored at room temperature after being packed in an unsealed plastic container for 3 months.  The experiment was conducted in Samsung /turkey, in Ondokuz Mayis university, Department of food Engineering labs. Chemical, physical, microbiological and sensory analysis of raw and dried yoghurt   samples were performed before and during storage. The results of the study showed that drying significantly affects all properties of yoghurt. The moisture content (1%) was affected by drying as moisture decreased by great rate of more than (70%) (P ≤ 0.05) , moisture was also affected by small amount by the storage; Protein content % was significantly increased by drying from (4.020%) in the raw yoghurt produced during production shelf life, and (3.217%) in the yoghurt produced after expiration date to (7.177%) in average, the protein content values were not affected by the storage in the dried samples by the spray drying method. Drying significantly (P ≤ 0.05) affect the values of fat content where the values increased after expiration date to (13%) in average, and the value were not affected by the storage. The non-fatty solids content significantly (P ≤ 0.05) increased by drying, has become an average of (77.00%) after drying. Acidity value ratio increased by drying and storage by meager percentage, the pH value significantly decreased (P ≤ 0.05) by drying and storage at a significantly rate. Total Solids % was significantly affected (P≤0.05) by drying and storage as it increased from (16.42%) in the raw yoghurt (during production shelf life) and (14.69%) in the raw yoghurt (after expiration date) to become more than (90%) by drying. As for the microbial content; the total bacteria value decreased by drying, but were not affected by storage, also lactic acid bacteria values reduced significantly (P ≤ 0.05) by drying, but remained the same during storage. However, the total count of yeast, molds, E-coli bacteria was not found in the raw yoghurt and has not grown during storage. In the sensory evaluation, the panelists preferred a raw yoghurt and dried yoghurt in the first month, and then the rate and values of the sensory evaluation decreased significantly (P ≤ 0.05) during storage. The study concluded that, the validity of yoghurt can be extended by drying, and taking advantages of yoghurt in the last day by drying and storing it.